Process analysis of variables for standardization of antifungal susceptibility testing of nonfermentative yeasts (2011)
ABSTARCT: Nonfermentative yeasts, such as Cryptococcus spp., have emerged as fungal pathogens during the last few years. However, standard methods to measure their antifungal susceptibility (antifungal susceptibility testing [AST]) are not completely reliable due to the impaired growth of these yeasts in standard media. In this work, we have compared the growth kinetics and the antifungal susceptibilities of representative species of nonfermentative yeasts such as Cryptococcus neoformans, Cryptococcus gattii, Cryptococcus albidus, Rhodotorula spp., Yarrowia lipolytica, Geotrichum spp., and Trichosporon spp. The effect of the growth medium (RPMI medium versus yeast nitrogen base [YNB]), glucose concentration (0.2% versus 2%), nitrogen source (ammonium sulfate), temperature (30°C versus 35°C), shaking, and inoculum size (10(3), 10(4), and 10(5) cells) were analyzed. The growth rate, lag phase, and maximum optical density were obtained from each growth experiment, and after multivariate analysis, YNB-based media demonstrated a significant improvement in the growth of yeasts. Shaking, an inoculum size of 10(5) CFU/ml, and incubation at 30°C also improved the growth kinetics of organisms. Supplementation with ammonium sulfate and with 2% glucose did not have any effect on growth. We also tested the antifungal susceptibilities of all the isolates by the reference methods of the CLSI and EUCAST, the EUCAST method with shaking, YNB under static conditions, and YNB with shaking. MIC values obtained under different conditions showed high percentages of agreement and significant correlation coefficient values between them. MIC value determinations according to CLSI and EUCAST standards were rather complicated, since more than half of isolates tested showed a limited growth index, hampering endpoint determinations. We conclude that AST conditions including YNB as an assay medium, agitation of the plates, reading after 48 h of incubation, an inoculum size of 10(5) CFU/ml, and incubation at 30°C made MIC determinations easier without an overestimation of MIC values.